2010
DOI: 10.1016/j.jmwh.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Coping With Labor Algorithm: An Alternate Pain Assessment Tool for the Laboring Woman

Abstract: The documentation of pain in the labor and delivery setting is one of the essential tasks of all health care providers who care for women in labor. The Joint Commission standards mandate regular pain assessments, but compliance with this mandate in the highly unique patient population of laboring woman is problematic when using the standard 0 to 10 Numeric Rating Scale. Labor pain is always unique given the various contributing physiologic, emotional, social, and cultural components. This article describes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 34 publications
(79 reference statements)
1
42
0
6
Order By: Relevance
“…It is also fortified by the theory that decreased nerve conduction velocity, attenuation or block of pain conduction to central nervous system via gate control theory, mind deviation from pain, and decreased muscle stretch which all result in increase in pain perception threshold. [30] This result is in accordance with finding of Dehcheshmeh et al (2009). [31] They found that parturient who had been given ice application experienced highly significant and considerable relief of pain than the control group (P < .001).…”
Section: Discussionsupporting
confidence: 92%
“…It is also fortified by the theory that decreased nerve conduction velocity, attenuation or block of pain conduction to central nervous system via gate control theory, mind deviation from pain, and decreased muscle stretch which all result in increase in pain perception threshold. [30] This result is in accordance with finding of Dehcheshmeh et al (2009). [31] They found that parturient who had been given ice application experienced highly significant and considerable relief of pain than the control group (P < .001).…”
Section: Discussionsupporting
confidence: 92%
“…Fase laten adalah fase awal, dimulai pada saat adanya kontraksi yang teratur , servik berdilatasi dari 0 sampai 3 cm (Pillitteri, 2009). Fase ini berlangsung sekitar 8 -10 jam pada primipara dan 6 sampai 8 jam pada nulipara (Pillitteri, 2009).…”
Section: Pendahuluanunclassified
“…The recently developed pain assessment tool for laboring women, the Coping with Labor Algorithim, is useful to discern whether women need intervention for pain and offers nonpharmacological care methods that nurses can suggest to laboring women (Gulliver, Fisher, & Roberts, 2008;Roberts, Gulliver, Fisher, & Cloyes, 2010). Penny Simkin also developed pain and coping rating scales that may be useful (Simkin & Hull, 2011).…”
Section: Caregiver Education Assessment and Supportmentioning
confidence: 99%